Averaging of a multipoint problem with parameters for an impulsive oscillation system - Petryshyn, Ya. R. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
By using the averaging method, we prove the solvability of a multipoint problem with parameters for a nonlinear oscillation system with pulse influence at fixed times. We establish estimates for the deviation of solutions of the original and averaged problems.